Erlebnisse und Rezeption Krležas Kerempuh-Balladen aus ungarischer Sicht - Lokös, István (Vortraege und Abhandlungen zur Slavistik, 1999)
The comparative analysis of the Ady poem "Sírni, sírni, sírni" and the Krleža poem "Tužaljka nad crkvom" convincingly proves the paraphrasic character of the latter and thus the creative reception of the poem of Ady. With the comparative investigation of the motif world and the linguistic archaisms of Ady and Krleža, the facts of the Ady reception, which are everywhere present in the Kerempuh ballads, are made visible.